Implementation of guidelines on Family Involvement for persons with Psychotic disorders: a pragmatic cluster randomized trial. Effect on relatives’ outcomes and family interventions received - Norheim, Irene; Pedersen, Reidar; Selle, Maria Lie; Røssberg, Jan Ivar; Hestmark, Lars; Heiervang, Kristin Sverdvik; Ruud, Torleif; Åsholt, Vilde Maria; Hansson, Kristiane Myckland; Møller, Paul; Fosse, Roar; Romøren, Maria (Frontiers in Psychiatry, 2024)
Background: Family interventions (FI) are recommended as part of the treatment for psychotic disorders, but the implementation in mental health services is generally poor. Recently, The Implementation of guidelines on Family Involvement for persons with Psychotic disorders (IFIP) trial, demonstrated significant improvements in implementation outcomes at cluster-level. This sub-study aims to examine the impact effectiveness of the IFIP trial intervention on the level of FI provided and on relatives’ outcomes and received FI. Methods: A cluster randomized controlled trial, including both implementation interventions and clinical interventions, was conducted in 15 Norwegian Community Mental Health Center (CMHC) units that were randomizedly assigned to either the IFIP intervention, including implementation interventions and clinical interventions, or treatment as usual (TAU). The clinical interventions consisted of FI: basic family involvement and support (BFIS) to all patients and family psychoeducation (FPE) to as many as possible. Patients with psychotic disorders and their closest relative were recruinvited to fill in questionnaires at inclusion and 6 months and 12 months follow-up. Received FI was reported by both relatives and clinicians. The relatives’ primary outcome was satisfaction with health service support, measured by the Carer well-being and support questionnaire part B (CWS-B). The relatives’ secondary outcomes were caregiver experiences, expressed emotions and, quality of life and FI received. Patients' outcomes will be reported elsewhere. Results: In total 231 patient/relative pairs from the CMHC units were included (135 intervention; 96 control). The IFIP intervention The relatives in the intervention arm received an increased in the level of BFIS (p=.007) and FPE (p < 0.05) compared to the relatives in the control arm, including relatives’ involvement in crisis planning. The primary outcome for relatives’ satisfaction with health service support, showed a non-significant improvement (Cohen’s d = 0.22, p = 0.08). Relatives experienced a significant reduced level of patient dependency (Cohen’s d = -0.23, p = 0.03). NB! I encountered problems with the abstract. It was rejected despite having only 339 words. To proceed with the submission, the conclusion has now been excluded from the abstract.